2016
DOI: 10.1098/rsif.2016.0823
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate receptor 1 regulates the directional migration of lymphatic endothelial cells in response to fluid shear stress

Abstract: The endothelial cells that line blood and lymphatic vessels undergo complex, collective migration and rearrangement processes during embryonic development, and are known to be exquisitely responsive to fluid flow. At present, the molecular mechanisms by which endothelial cells sense fluid flow remain incompletely understood. Here, we report that both the G-protein-coupled receptor sphingosine 1-phosphate receptor 1 (S1PR1) and its ligand sphingosine 1-phosphate (S1P) are required for collective upstream migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…4). We have previously observed that HLMVECs migrate against the direction of flow 24,30,31 . Here, we observed that, in the presence of flow, HLMVECs moved towards the constriction site (x-direction) but did not show migration in the direction of flow (y-direction) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…4). We have previously observed that HLMVECs migrate against the direction of flow 24,30,31 . Here, we observed that, in the presence of flow, HLMVECs moved towards the constriction site (x-direction) but did not show migration in the direction of flow (y-direction) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Determination of cell migration: brightfield movies were processed in the same way as our previous publications 24,30 . Movies were processed with Fiji software and analyzed using custom Matlab routines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these same cells at lower density exhibited the opposite behavior by moving with the direction of flow. Using a similar in vitro system, Surya et al demonstrated that S1P signaling is involved with the collective migration of LECs.…”
Section: Lymphatic Vessel Physiology Function and Lymphangiogenesismentioning
confidence: 99%
“…In areas of laminar flow with high shear stress, S1P1 is present on the membrane, whereas it is internalized in areas of disturbed flow with low shear stress. S1P1 regulates the directional migration of lymphatic endothelial cells in response to fluid shear stress, which is required plasma or S1P [77]. The change in S1P1 might associate with remodeling of the glycocalyx.…”
Section: New Insights On Endothelial Glycocalyx and Atherosclerosismentioning
confidence: 99%